Глухівщина кінця ХVІІІ ст. у документах фонду 206 ЦДІАК України - Тарасенко, І.Ю. (Сіверщина в історії України, 2021)
У статті на основі документальних джерел з фонду 206 ЦДІАК
України розглянуто процес закріпачення вільного населення на
території Глухівського повіту Новгород-Сіверського намісництва.
Зауважено, що притягненню у підданство піддавалися не тільки
селяни, а й козаки і міщани Глухова. У зв’язку з початком
ІV всеросійської ревізії 1781–1787 рр. піддані змушені були вдаватися
до різних способів уникнення залежності, у тому числі до масових
втеч. Стаття доповнена документами з фонду. In January 1782, the Novhorod-Siverskyi governorate was inaugurated.
This included the lands of the Starodub, Nizhyn and Chernihiv regiments,
divided into 11 counties, including Hlukhiv. The main array of sources on
the history of the governorship is stored in the Central State Historical
Archive of Ukraine in Kyiv (TsDIAK), primarily in the fund 206 (Novhorod-
Siverskyi governorship). It contains documents of the board for the years
1782–1797. There are 12,500 cases, the description of which is contained
in five volumes. The fund stores various cases (Senate decrees, reports,
statements, letters, complaints, etc.). There are especially many lawsuits
concerning land and other property conflicts. Among them are many relating
to conversion, escape, search, detention and return of fugitives. The task of
this work is to illustrate the scale and depth of the process of enslavement
of the Ukrainian population on the example of Hlukhiv and Hlukhiv district
of Novhorod-Siverskyi governorship and passive resistance to this process
in the final liquidation of the Hetmanate. There were about 160 such
cases in the fund in 1782 alone (along with several cases of disobedience
to landlords and persuasion to flee). This is due to the beginning of the IV
All-Russian revision of the taxable population in 1781–1787 under the
leadership of the Senate. The nobility, officials of various kinds, the military,
the clergy - the largest landowners in the county, sought to record in their
fairy tales as many subjects. This created the basis for corruption, abuse
of power, caused conflicts and judicial investigations, refusal to perform
citizenship, mass flight of citizens. It should be noted that not only peasants
but also Cossacks and burghers of Hlukhiv were subjected to citizenship
and enslavement. At this time, the number of requests from residents of the
city and its environs to enroll in the bourgeois state increased significantly,
to which the attention of the governor’s board was paid by the Hlukhiv
commandant E. Prostokvashyn. The governor’s board was overwhelmed
with complaints and requests to find and return fugitives from such
landowners as Myklashevskyi, Borzakovskyi, Dergun, Skoropadskyi, Count
K. Rozumovskyi, Prince Bariatynski, etc., which testified to the spread and
final establishment of serfdom in Ukraine on the Left.